Analysis of the Various Elements of Heat Sources in Silicon Carbide Polymers (6H-SiC and 3C-SiC) Semiconductor Laser - Marjani, Saeid; Faez, Rahim; Marjani, Hamid (Asian Journal of Chemistry, 2012)
In the present paper, we investigated the various elements of heat sources within a silicon carbide polymers (6H-SiC and 3C-SiC) semiconductor laser. The device employs 3C-SiC quantum well (QW) which is sandwiched between two layers of 6H-SiC as cladding regions that can be interpreted in terms of a type-II heterostructure character and a built-in electric field due to the pyroelectricity of 6H using a numerical simulator. The basic design goal was the study of the various elements of heat sources, including the Joule heat power, the Peltier-Thomson heat power and the recombination heat power.